2005
DOI: 10.1523/jneurosci.2032-05.2005
|View full text |Cite
|
Sign up to set email alerts
|

Fear Conditioning following Unilateral Temporal Lobectomy: Dissociation of Conditioned Startle Potentiation and Autonomic Learning

Abstract: The present study investigated fear-potentiated startle and autonomic learning in brain-lesioned patients in a classical fear-conditioning paradigm. Startle blink and skin conductance responses of 30 patients who underwent unilateral temporal lobectomy because of drugresistant epilepsy were compared with those of 32 healthy controls. As expected, temporal lobectomy patients showed a general impairment in fear conditioning relative to controls. This impairment did not differ with respect to the affected hemisph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
66
2

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(75 citation statements)
references
References 38 publications
7
66
2
Order By: Relevance
“…Responses to tactile (e.g., an airpuff to the throat or face) or acoustic stimuli are recorded in animals as a whole body "flinch response" and in humans as the strength of the eye blink response (EMG electrodes at the orbicularis oculi muscles). Cortical and limbic brain regions, many of which are abnormally activated or exhibit altered volumes in anxiety disorders (as measured by fMRI or PET e.g., Gilbertson et al, 2002;Hull, 2002;Lorberbaum et al, 2004;Neumeister et al, 2004;Schneider et al, 1999), modulate startle responses (Davis, 1998;Funayama et al, 2001;Kumari et al, 2003;Swerdlow et al, 2001;Weike et al, 2005). The magnitude of the response is highly plastic: fear-inducing stimuli (termed fear-potentiated startle; FPS) or administration of anxiogenic compounds, such as CRF, increases startle (Brown et al, 1951;Davis et al, 1997;Swerdlow et al, 1986), while threat-reducing stimuli (Lang et al, 1990), anxiolytic and sedative drugs (Abduljawad et al, 2001) or sensory input in the case of prepulse inhibition (PPI) Geyer et al, 2001;Graham, 1975;Swerdlow et al, 2001) reduces startle.…”
Section: The Startle Responsementioning
confidence: 99%
“…Responses to tactile (e.g., an airpuff to the throat or face) or acoustic stimuli are recorded in animals as a whole body "flinch response" and in humans as the strength of the eye blink response (EMG electrodes at the orbicularis oculi muscles). Cortical and limbic brain regions, many of which are abnormally activated or exhibit altered volumes in anxiety disorders (as measured by fMRI or PET e.g., Gilbertson et al, 2002;Hull, 2002;Lorberbaum et al, 2004;Neumeister et al, 2004;Schneider et al, 1999), modulate startle responses (Davis, 1998;Funayama et al, 2001;Kumari et al, 2003;Swerdlow et al, 2001;Weike et al, 2005). The magnitude of the response is highly plastic: fear-inducing stimuli (termed fear-potentiated startle; FPS) or administration of anxiogenic compounds, such as CRF, increases startle (Brown et al, 1951;Davis et al, 1997;Swerdlow et al, 1986), while threat-reducing stimuli (Lang et al, 1990), anxiolytic and sedative drugs (Abduljawad et al, 2001) or sensory input in the case of prepulse inhibition (PPI) Geyer et al, 2001;Graham, 1975;Swerdlow et al, 2001) reduces startle.…”
Section: The Startle Responsementioning
confidence: 99%
“…Numerous patients reported the emotion of fear prior to seizures (2). Mesial temporal lobe epilepsy is commonly associated with ictal fear (3), and temporal lobectomy patients showed a general impairment in fear conditioning (4,5). However, the association between seizure-modulated fear and the underlying basics of neuronal mechanisms remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, Baker and Kim (2004) observed that in rats, posttraining lesions to the right amygdala lead to a considerably larger impairment in (Buchanan, Tranel, & Adolphs, 2006). Damage to the right amygdala also has been observed to produce a more global deficit in electrodermal responses than damage to the left amygdala (Gläscher & Adolphs, 2003;Weike et al, 2005), perhaps reflecting an asymmetry in global autonomic control.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, Baker and Kim (2004) observed that in rats, posttraining lesions to the right amygdala lead to a considerably larger impairment in (Buchanan, Tranel, & Adolphs, 2006). Damage to the right amygdala also has been observed to produce a more global deficit in electrodermal responses than damage to the left amygdala (Gläscher & Adolphs, 2003;Weike et al, 2005), perhaps reflecting an asymmetry in global autonomic control.Neuroimaging data have also pointed to functional asymmetries in amygdalar function. Several studies suggest that the right amygdala responds more to experientially learned or conditioned fearful stimuli, whereas, the left amygdala appears more active during the perception of innately fear-related items such as photographs of threatening stimuli or fearful faces (e.g., Büchel et al, 1998;Dolan and Morris, 2000;Morris et al, 1996Morris et al, , 1998.…”
mentioning
confidence: 99%
See 1 more Smart Citation